Exploring nanoporous carbon architectures for enhanced solid-state hydrogen storage: Recent progress and future prospects - Hossain M.A.M.; Hannan M.A.; Tiong S.K.; Ker P.J.; Abu S.M.; Wong R.T.; Mahlia T.M.I. (Elsevier Ltd, 2025)
Hydrogen (H2), with the highest energy density among energy carriers, is crucial for advancing renewable energy. Efficient H2 storage is key to transitioning to renewable sources. Solid-state H2 storage (SSHS) technology, known for its high energy density, safety, and cost-effectiveness, is emerging as a vital method. However, finding the most efficient SSHS materials to meet remains an open question, requiring new strategies for material design. Among various investigated materials, nanoporous carbon architectures (NCAs) are promising due to their high surface area, adjustable pore structure, and excellent chemical stability. This review highlights recent advancements in optimizing nanoporous carbon materials (NCMs), specifically NCAs, through advanced synthesis techniques to enhance their practical potential for SSHS. It covers H2 storage fundamentals, including the impact of pore size and surface chemistry, alongside strategies to improve storage capacity and kinetics. Additionally, it addresses challenges such as limited storage capacity, slow reaction kinetics, and long-term stability, as well as promising approaches to advance SSHS. The paper emphasizes the need for further research to optimize pore structures, increase binding energy, and conduct comprehensive lifecycle analyses. These efforts are essential for transitioning to a sustainable H2 economy and ensuring the commercial viability of NCAs in H2 storage applications. Overall, the results indicate that addressing the current challenges and leveraging the unique properties of NCAs can lead to effective H2 storage methods, contributing to the broader adoption of H2 as a clean energy carrier. ? 2025 Hydrogen Energy Publications LLC